The Analysis Study of Impact of Anesthesia on Patients with Cardiovascular Disease: A Comprehensive Systematic Review - Arkanditya Putra Tohas; Yuni Nurjanah (International Medical Journal Corp. Ltd, 2025)
Background: Anesthesia is a cornerstone of modern surgery, providing the necessary sedation, pain control, and muscle relaxation that make complex procedures possible. However, its effects extend far beyond simply putting patients to sleep, particularly in those with preexisting cardiovascular disease. This systematic review aims to synthesize current evidence regarding the impact of anesthesia on patients with cardiovascular disease. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Anesthesia significantly impacts patients with CVD, requiring careful selection of agents and techniques to minimize perioperative risks. Volatile anesthetics improve outcomes in cardiac surgery, while conscious sedation offers advantages in TAVR procedures. α2-Adrenoceptor agonists, EEG-guided anesthesia, and multidisciplinary perioperative management are essential for optimizing patient outcomes. Further research is needed to enhance perioperative care for this high-risk population.